METHODOLOGICAL BASES OF OPTIMIZATION OF THE RISK MANAGEMENT PROCEDURE - T. V. Naumova (Научный вестник МГТУ ГА, 2016)
The article considers risk as a social phenomenon in historical and philosophical perspective, analyses the risk management principles approved by national and international standards in the field of risk management. It also identifies weaknesses in existing procedures and provide recommendations for their optimization. The author focuses on the importance of philosophical reflection interdisciplinary approaches to the problem of security.